2006
DOI: 10.1158/1078-0432.ccr-05-2096
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Aberrant DNA Methylation in Helicobacter pylori–Infected Gastric Mucosae and its Possible Association with Gastric Cancer Risk

Abstract: Introduction: Risk prediction of gastric cancers is important to implement appropriate screening procedures. Although aberrant DNA methylation is deeply involved in gastric carcinogenesis, its induction by Helicobacter pylori, a strong gastric carcinogen, is unclear. Here, we analyzed the effect of H. pylori infection on the quantity of methylated DNA molecules in noncancerous gastric mucosae and examined its association with gastric cancer risk. Experimental Design: Gastric mucosae were collected from 154 hea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
525
4
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 585 publications
(563 citation statements)
references
References 25 publications
32
525
4
2
Order By: Relevance
“…Moreover, inflammatory processes repress the expression of a number of genes and methylation is known to be promoted by the decrease in gene expression [25]. Similar results to those found in our study were also reported by Lui et al In their study, Lui et al…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, inflammatory processes repress the expression of a number of genes and methylation is known to be promoted by the decrease in gene expression [25]. Similar results to those found in our study were also reported by Lui et al In their study, Lui et al…”
Section: Discussionsupporting
confidence: 92%
“…Abnormal methylations in promoter regions of several genes are induced by H. pylori in gastric mucosa including cell growth-related genes p16(INK4a), p14(ARF), and APC; DNArepair genes, hMLH1, BRCA1, and MGMT; the cell adherence gene E-cadherin; as well as LOX, FLNC, HRASLS, HAND1, THBD, and p41ARC, which are known to be methylated in GC patients [22][23][24]. Individuals with H. pylori infection have increased level of gene methylations, which decrease in the absence of the bacteria, consistent with the notion that methylations are induced by the bacterial infection [4,22,24,25].…”
Section: Discussionsupporting
confidence: 70%
“…This result is consistent with those of previous studies that have demonstrated the close association of HP infection with aberrant CpG island hypermethylation. [25][26][27] We found that HP infection was a confounding factor in the comparison of methylation between CG and GCN and the analysis restricted to HP-positive cases did not show any difference in the number of methylated genes between CG and GCN. This was in contrast to the previous study of Waki et al, 28 who demonstrated higher number of methylated CpG island loci in GCN than in CG using MSP.…”
Section: Methylation In Gc Was Revealed For the First Time In Thismentioning
confidence: 66%
“…Recent studies exhibited a marked difference of methylation levels between CG and GCN in HP-negative cases but no difference between them in HP-positive cases. 27,29 The CpG island locus of CACNA1G corresponds to MINT31, which was used as one of the reference CpG island loci to determine CpG island methylator phenotype of GCs or colorectal carcinomas. 20,30,31 According to Toyota et al's 30 study using COBRA, MINT31 was never methylated in GC-associated normal stomach samples.…”
Section: Methylation In Gc Was Revealed For the First Time In Thismentioning
confidence: 99%
“…Helicobacter pylori (H. pylori) infection plays an important role in gastric cancer development [3][4][5]. H. pylori-infected gastric mucosa is characterized as chronic inflammation and atrophy [5], leading to epigenetic changes characterized by the promoter methylation of multiple genes [6,7]. This phenomenon can be explained by the concept of an "epigenetic-field-defect" which is linked to gastric cancer predisposition.…”
Section: Introductionmentioning
confidence: 99%